2014
DOI: 10.1016/j.oregeorev.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Geology and geochemistry of Middle Eocene Maden complex ferromanganese deposits from the Elazığ–Malatya region, eastern Turkey

Abstract: In the study region, the Pütürge Precambrian-Permian metamorphic rocks, the Upper Jurassic-Lower Cretaceous Guleman ophiolites, the Upper Cretaceous-Lower Eocene Hazar unit, the Campanian-Lower Maastrichtian aged Elazığ magmatics, and the Middle Eocene Maden complex crop out extensively. The Maden complex containing ferromanganese mineralization unconformably overlies the Pütürge metamorphic rocks, the Guleman ophiolites, and the Hazar unit and is unconformably overlain by Plio-Quaternary sediments. The ferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Bonatti et al (1972) confirmed that the two elements are found as a solid solution in the form of strontio-barite. The concentration of Ba in hydrothermal solution is higher relative to sea water due to the impact of volcanic activity (Monnin et al 2001;Oksuz 2011;Sasmaz et al 2014), which still points to the dominant hydrothermal influence on Enkafela Mn deposit. The concentration of transition metals like Ni, Zn, Co and Cu is also utilised to understand the source and depositional mechanism of manganese deposits (Bonatti et al 1972;Toth 1980;Kahrazehi et al 2015).…”
Section: Genesis Deduced From Major and Trace Element Geochemistrymentioning
confidence: 99%
“…Bonatti et al (1972) confirmed that the two elements are found as a solid solution in the form of strontio-barite. The concentration of Ba in hydrothermal solution is higher relative to sea water due to the impact of volcanic activity (Monnin et al 2001;Oksuz 2011;Sasmaz et al 2014), which still points to the dominant hydrothermal influence on Enkafela Mn deposit. The concentration of transition metals like Ni, Zn, Co and Cu is also utilised to understand the source and depositional mechanism of manganese deposits (Bonatti et al 1972;Toth 1980;Kahrazehi et al 2015).…”
Section: Genesis Deduced From Major and Trace Element Geochemistrymentioning
confidence: 99%
“…The eastern part is instead dominated by the Late Cretaceous Ispendere ophiolites and the Middle Eocene Maden Complex. The former exhibit an intact ophiolitic sequence intruded by granites [ 82 ], the latter a volcanosedimentary sequence with conglomerates, sandstones, limestones, mudstones, spilitic lavas, radiolarites, cherts, altered basalts and andesites [ 80 , 81 , 83 ].…”
Section: Geological Setting and Raw Materials Supplymentioning
confidence: 99%
“…Yılmaz [2], bölgeyi üç tektonik birime ayırmıştır: (I) Arap platformu, (II) bindirme bölgesi, (III) nap 681 bölgesi. GAOK, (1) Malatya, Keban, Engizek ve Binboğa masifleri dâhil olmak üzere Güneydoğu Anadolu'nun Neoproterozoik-Triyas metamorfik masiflerinden [3][4][5]; (2) Geç Kretase okyanus içi yay sistemi birimlerinden (ofiyolitler ve yay tipi/çarpışma sonrası magmatik kayaçlar) [6][7][8][9][10][11][12][13][14][15] ve (3) Geç Kretase-Kuvaterner yaşlı volkanik ve sedimanter kayaçlarından oluşmaktadır [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionunclassified